Критерий выбора коэффициента преломления света для полимерных оболочек оптического волокна - Щебенюк, Леся Артемовна; Петренко, О. И.; Удовенко, И. И. (НТУ "ХПИ", 2014)
Выполнен анализ результатов сравнения свойств кабельных полимеров для применения в оптических кабелях. Различные фирмы производители оптического волокна предлагают использование оптического волокна с различными коэффициентом преломления n1. При этом возникает вопрос о соответствующем выборе коэффициента преломления n2 для полимерной оболочки, поскольку разность n1 – n2 определяет большинство эксплуатационных характеристик оптического кабеля.

In the design and selection of the cable polymeric materials, in selecting the optimum material for a particular promeneniya always a problem limiting the spectrum of material parameters .The analysis of the results of the comparison of cable properties of polymers for use in optical cables is .presented. Various company manufacturers suggest the use of optical fiber optical fiber with different refractive index n1. This raises the question of choosing the appropriate refractive index n2 for the polymeric shell as the difference n1 - n2 defines the majority of operating characteristics of the optical cable. For branched chains optical network for a given value of the refractive index the range of values for the refractive index of the polymer shell tapers rapidly increasing branching.
Selection criteria for refractive index of polymer shells of optical fiber
Keywords: оптические кабеля; кабельные полимеры; коэффициент преломления; параметры оптического волокна; cable polymers; refractive index; optical fiber parameters